2010
DOI: 10.3851/imp1676
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and in Vivo Anti-Influenza Virus Activity of Diarylheptanoids Isolated from Alpinia Officinarum

Abstract: AO-0002 was suggested to have a different anti-influenza virus action to that of oseltamivir and was verified to show anti-influenza activity in vitro and in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 28 publications
0
36
0
Order By: Relevance
“…Thus, a recent paradigm shift includes the search and quest for antiviral, redox regulator and/or anti-inflammatory strategies that could either solely emerge as new antiinfluenza or adjunct therapy combined with the existing arsenal to reduce the severity and complications of influenza infections (1,5,14,18,(45)(46)(47)(48). Data from a number of studies suggest that the use of oxygen free radicals as targets may provide an approach to the amelioration of the pathogenicity caused by influenza virus infections (15,47), and several studies have reported the anti-influenza activity of medicinally potent and disease-preventing plant polyphenols and flavonoids with antioxidant properties (9,17,24,42,47,48).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a recent paradigm shift includes the search and quest for antiviral, redox regulator and/or anti-inflammatory strategies that could either solely emerge as new antiinfluenza or adjunct therapy combined with the existing arsenal to reduce the severity and complications of influenza infections (1,5,14,18,(45)(46)(47)(48). Data from a number of studies suggest that the use of oxygen free radicals as targets may provide an approach to the amelioration of the pathogenicity caused by influenza virus infections (15,47), and several studies have reported the anti-influenza activity of medicinally potent and disease-preventing plant polyphenols and flavonoids with antioxidant properties (9,17,24,42,47,48).…”
Section: Introductionmentioning
confidence: 99%
“…When diarylheptanoids isolated from Alpinia officinarum were orally administered to mice infected with influenza A virus, these aromatic compounds significantly reduced body weight and prolonged survival times of infected mice and also reduced viral titers in bronchoalveolar lavage fluids of the lungs. These compounds demonstrated dose-dependent suppression of viral messenger RNA [52].…”
Section: Interfering Virus Replication or Suppressing Viral Rna Synthmentioning
confidence: 98%
“…The anticancer activity of diarylheptanoids isolated from Alpinia officinarum has been reported (8,(9)(10)(11)(12)(13)(14)(15)17,18,28). Table 3 summarizes the biological effects of the main diarylheptanoids purified from the plant.…”
Section: Lesser Galangal Arrests Tumor Cell Growth and Proliferation:-mentioning
confidence: 99%
“…More recently, many unique biochemical compounds have been purified from A. officinarum (6,7). Among the most studied of these compounds are galangin and members of a class of compounds known as diarylheptanoids which have been demonstrated to have significant anti-inflammatory, anti-proliferative and anti-emetic properties (3,(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) (Tables 2 and 3).…”
Section: Introductionmentioning
confidence: 99%